Time's river : archaeological syntheses from the lower Mississippi River Valley - Rafferty, Janet, 1947-; Peacock, Evan, 1961- (University of Alabama Press, 2008)
Serves as a resource for archaeologists working in the region extending from Louisiana through Mississippi north to Missouri and Kentucky. This title examines the matters of method and theory, the application of materials science, geophysics, and other tools in archaeology that provide for better data-recovery.